(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Scientific creativity meanscreative work in sphere of science. All inventions, innovations, discoveries inscience consider scientific creativity. They think differently from common manand open new ways of living and survive. Only few people come in this categoryi.e. Newton, A P J Abdul kalam, Darwin etc gave their matchless creation to theworld. This is the era of science and technology so it is vary necessary to seethe creative potential of students in this area so that we can encouragestudents to show their ability in this area To observe the creative potentialof Scheduled caste students in science scientific creativity test (1971) byKaruna Sanker Mishara was used. Ideational fluency, Originality andflexibility were assessed through this test. Results of Scientific creativityare given as under.